Die Matrikel der Wiener Rechtswissenschaftlichen Fakultät Matricula Facultatis Juristarum Studii Wiennensis - Mühlberger, Kurt (2011)
The first volume of the University of Vienna Matriculation Book of the Faculty of Law includes the period from 1402 to 1442. It represents the oldest record of the history of scholarly lawyers in the German language area, and is a first-class source for studies of the history of persons and the institution of the Faculty of Law, as well as the social history of late medieval scholarly world. The register book ("album") of the Faculty of Law contains not only the registration at entry, but also the date of graduation. Therefore one can determine the duration of studies in each case, and the most important data on the curriculum of enrolled students are preserved. In addition, the book contains information on the regional and social origins of university students and on the level of their respective matriculation fees. Apart from the critical edition of the matriculation text, the volume also includes a list of deans . Moreover it is accompanied by indices of persons and places, as well as information about contemporary sources on the University of Vienna.